Isolation and selection of efficient ohosphofungi from rubber plantations - Joseph K; Jose G; Philip S (Rubber Science)
Twenty five phosphofungal isolates from rubber (Hevea brasiliensis) plantations were evaluated for solubilization of ferric phosphate, aluminium phosphate, tricalcium phosphate fertilizer grade rock phosphate and acid phosphatase activity. Among the twenty five, seven isolates showed solubilization of phosphates and fertilizer grade rock phosphate and belonged to Aspergillus spp. and Penicillium spp. and was selected for further studies. These selected isolates were further evaluated for its beneficial effect on growth of rubber seedlings raised on root trainer cups. Among the seven, one isolate, Penicillium spp. (Pf 11) was further evaluated for growth improvement in root trainer plants in combination with 25, 50 and 100 per cent of the recommended dose of fertilizer and compared with uninoculated plants with 25, 50 and 100 per cent of fertilizer. The plants inoculated with Pf 11 at 50 per cent fertilizer showed higher girth, height and root development followed by inoculation with Pf 11 at 25 per cent fertilizer level. Girth of plants in treatment wit Pf 11 at full fertilizer was lower than the treatment with 25 and 50 per cent fertilizer application in combination with inoculation. Highest population of inoculated phospho fungi was at 25 per cent fertilizer application and was reduced as the fertilizer levels increased. An efficient phosphofungus (Pencillium spp) could be isolated from the rubber plantations and upon inoculation in rubber seedlings recorded better growth at 50 per cent of the recommended level of fertiliser.
Keywords: Hevea brasiliensis; Penicillium spp; Phosphorus solubilization; Photofungi